Artificial intelligence and consent: A feminist anti-colonial critique - Joana Varon; Paz Pe\~na (Internet Policy Review, 2021)
Feminist theories have extensively debated consent in sexual and political contexts. But what does it mean to consent when we are talking about our data bodies feeding artificial intelligence (AI) systems? This article builds a feminist and anti-colonial critique about how an individualistic notion of consent is being used to legitimate practices of the so-called emerging Digital Welfare States, focused on digitalisation of anti-poverty programmes. The goal is to expose how the functional role of digital consent has been enabling data extractivist practices for control and exclusion, another manifestation of colonialism embedded in cutting-edge digital technology.
Keywords: 300; Artificial intelligence; Colonialism; Consent; Feminism; Data protection